The effect of two different types of removable partial dentures on chewing activity and muscle efficiency. - Banu Hiwa Mohammed; Rizgar Mohammedameen Hasan (Erbil Dental Journal)
Background and objectives: Cobalt chromium removable partial denture has been in use for years and despite of the advantages that cobalt chromium provides, it has many disadvantages. In the recent years flexible removable partial denture has been introduced to dentistry with many advantages over cobalt chromium removable partial denture . The purpose of this study was to evaluate the effect of cobalt chromium and flexible removable partial denture on chewing activity and muscle efficiency. Methods: Ten patients were selected, all of them had completely edentulous maxilla and Kennedy Class I partially edentulous lower arch. eight male and two females with their ages ranging from 45 to 60 years. For each patient, an upper complete denture and two lower removable partial dentures (cobalt chromium and flexible) were constructed. Once the dentures were completed, muscle efficiency with the use of Electromyography and chewing activity by sieving method was performed in scheduled visits. Statistical analysis of data was achieved by means of (SPSS 25). And performing (independent sample T test, one‐way anova test, and multiple comparison Tukey test). Results: The chewing activity test, revealed a statistically significant difference (P< 0.05) between first and fourth visit concerning the flexible partial denture and improvement of chewing, for the cobalt chromium removable partial denture although there was improvement of chewing but it was not significant. Regarding the muscle efficiency test, this test revealed that there was no major significance between flexible and cobalt chromium removable partial denture and they are almost the same, but we can notice improvements of muscular efficiency specially in masseter muscle. Conclusions: Within the limitations of this study, it has been concluded that the muscle efficiency is improved within one month of insertion of both types of removable partial denture . Both flexible and cobalt chromium dentures increased muscle efficiency. Flexible removable partial denture increased chewing activity slightly better than cobalt chromium, while cobalt chromium was marginally better at chewing of hard food comparing to flexible denture. Keywords: Surface electromyography, cobalt chromium, chewing, fexible denture.